Tingkat Kesehatan Koperasi Simpan Pinjam dan Faktor yang Mempengaruhinya - Nurita Indriawati; Agung Winarno; Trisetia Wijijayanti (Ekonomi Bisnis, 2017)
Abstract: The purpose of this study is to describe the health level of Savings and Loans Cooperative (KSP) in Malang City based on seven aspects, such as capital, productive asset quality, management, efficiency, liquidity, independence and growth, cooperative identity, and also analyzing the factors that influence it. Quantitative descriptive research using to documentation method in the form of annual, the financial report shows that (1) Capital in KPS is in healthy condition (2) quality of productive assets is in unhealthy condition (3) management is in healthy condition (4) efficiency is in unhealthy condition 5) liquidity is in unhealthy condition (6) independence and growth are in unhealthy condition, and the last one (7) cooperative identity is in unhealthy condition. Factors was affecting the KSP health is include negligence of members paying loan installments and mandatory savings, lack of cooperative readiness in long-term work planning, decreasing number of members, high burden, high loan interest rate and low deposit interest rate.Keywords: influencing factors, health level of Savings and Loans Cooperative Abstrak: penelitian ini bertujuan untuk mendeskripsikan tingkat kesehatan Koperasi Simpan Pinjam (KSP) di Kota Malang berdasarkan tujuh aspek antara lain permodalan, kualitas aktiva produktif, manajemen, efisiensi, likuiditas, kemandirian dan pertumbuhan, jati diri koperasi, serta menganalisis faktor yang mempengaruhinya. Penelitian deskriptif kuantitatif yang menggunakan metode dokumentasi berupa laporan keuangan tahunan ini menunjukkan bahwa (1) permodalan KSP berada pada kondisi sehat (2) kualitas aktiva produktif dalam kondisi kurang sehat (3) manajemen dalam kondisi cukup sehat (4) efisiensi dalam kondisi kurang sehat (5) likuiditas dalam kondisi kurang sehat (6) kemandirian dan pertumbuhan dalam kondisi kurang sehat (7) jati diri koperasi dalam kondisi tidak sehat. Faktor yang mempengaruhi kesehatan KSP antara lain kelalaian anggota membayar angsuran pinjaman dan simpanan wajib, kurangnya kesiapan koperasi dalam perencanaan kerja jangka panjang, penurunan jumlah anggota, beban yang tinggi, tingginya suku bunga pinjaman dan rendahnya suku bunga simpanan. Kata kunci: faktor yang mempengaruhi, kesehatan koperasi simpan pinjam